2017
DOI: 10.1038/s41467-017-01791-y
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved diffraction of shock-released SiO2 and diaplectic glass formation

Abstract: Understanding how rock-forming minerals transform under shock loading is critical for modeling collisions between planetary bodies, interpreting the significance of shock features in minerals and for using them as diagnostic indicators of impact conditions, such as shock pressure. To date, our understanding of the formation processes experienced by shocked materials is based exclusively on ex situ analyses of recovered samples. Formation mechanisms and origins of commonly observed mesoscale material features, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 36 publications
4
21
0
Order By: Relevance
“…Above this temperature threshhold, the requisite thermal energy is available to overcome an activation barrier, promoting small atomic displacements required to transform the highly- nanosecond timescales [25,64]. While the highest pressure datum in that study (34 ±5 GPa) overlaps our results, stishovite peaks were also observed at 19 GPa and below where we observe only amorphous material despite two orders of magnitude longer compression time.…”
supporting
confidence: 49%
“…Above this temperature threshhold, the requisite thermal energy is available to overcome an activation barrier, promoting small atomic displacements required to transform the highly- nanosecond timescales [25,64]. While the highest pressure datum in that study (34 ±5 GPa) overlaps our results, stishovite peaks were also observed at 19 GPa and below where we observe only amorphous material despite two orders of magnitude longer compression time.…”
supporting
confidence: 49%
“…Compression Sector (DCS) at the Advanced Photon Source (Argonne, IL) has linked a variety of planar shock compression drivers to a third-generation synchrotron light source -have provided new insights into a number of structural transformations [15][16][17][18]. Similarly, XRD measurements using an x-ray free electron laser have examined phase transformation in shorter duration shock wave experiments [19,20].…”
Section: Recent Experimental Advances Utilizing New Xrd Capabilities mentioning
confidence: 99%
“…These more extreme conditions drive a fraction of the matrix material into the β-quartz region of phase space. Figure 9 in the supplementary material shows the two calculated P-T states plotted on the phasediagram for silica, taken from Gleason et al 36 This result shows clearly that initial granular arrangement can have a marked response on the thermodynamic conditions in a shocked bimodal powder system.…”
Section: Figmentioning
confidence: 89%
“…Even at this extreme, the matrix material lies within the α-quartz region of silica phase space. 36 In the tomography-initialized simulations, however, the distribution of on-axis P-T conditions extend from a peak of (1.2 GPa, 798 K) to (2.1 GPa, 1385 K). These more extreme conditions drive a fraction of the matrix material into the β-quartz region of phase space.…”
Section: Figmentioning
confidence: 92%